Comparison of clinico-radiological profile of pulmonary tuberculosis in diabetic and non-diabetic patients in a tertiary care hospital – An observational analytical study - Asif Iqbal Biswas; Arindam Ray; Amitava Pal; Saikat Banerjee; Amiya Kumar Dwari (Asian Journal of Medical Sciences)
Background: Diabetes mellitus (DM) is becoming more widely acknowledged as a significant comorbidity that negatively affects outcomes of pulmonary tuberculosis (PTB), which remains a significant worldwide health burden. The interplay between TB and DM modifies clinical, microbiological, and radiological characteristics, necessitating detailed evaluation.